Otimização das condições de cultivo de Erysipelothrix rhusiopathiae para produção de vacina contra erisipela suína - Silva, Adilson José da (Universidade Federal de São Carlos, 2007)
Swine erysipelas is one of the diseases responsible for the great economic losses in swine-producing areas of the world. The bacteria Erysipelothrix rhusiopathiae is the causative agent of erysipelas, and the vaccines currently available for prevention of this disease are produced with the whole broth culture containing the inactivated microorganism or its live-attenuated form. A surface protein was identified as the main antigen. It can be found in the culture supernatant or attached to the cell wall through interactions with the choline residues from the teichoic and lipoteichoic acids of this structure. Considering the lack of information in the scientific literature about studies concerning the growth pattern of this pathogen, the company Vallèe S.A, a Brazilian industry of veterinary pharmaceutical products, established a partnership with researchers form the Chemical Engineering Department of UFSCar with the purpose of developing the technology required for the production of the cited vaccine. In this context, the objective of this work was to optimize the growing conditions of E. rhusiopathiae to establish a protocol for production of high cellular concentrations, enough to prepare a vaccine against swine erysipelas offering the same or a higher protection level compared to the commercially available formulations. To achieve this goal, the growth kinetics of this microorganism was investigated under different aeration conditions (aerobiosis, anaerobiosis and microaerophilic condition), changes in the medium nutrient s concentration were analyzed, and mice protection tests using the prepared vaccines were performed. The studies about the aeration influence on the microorganism growth and the antigen expression were made using a 4.0 L stirred-tank bioreactor, with an agitation frequency kept between 100 and 400 rpm and air or N2 flow rate of 1.0 L/min. The studies for the improvement of the medium formulation were carried out in flasks incubated at static condition or under agitation of 200 rpm. The vaccines were prepared using medium harvested in both conditions. The temperature was set at 37°C and the initial pH at 8,0 in all experiments. Samples of culture supernatant and from cell extracts made with choline chloride were analyzed by electrophoresis under denaturating conditions (SDS-PAGE) to evaluate the antigen expression. The preliminary electrophoresis results indicated that the antigen production is associated to the cell growth and its expression is favored in the presence of oxygen. Cellular concentrations around 1,8 g/L were reached, in all different aeration conditions employed, using the stirred-tank bioreactor operating with pH automatic control and using the culture medium with nutrients concentrations increased in 50 % from the Feist medium described in literature. The vaccines prepared in aerobic and microaerophilic condition led to higher protection levels in the challenge-exposure tests, and a formulation made from an aerobic culture in bioreactor having a cellular concentration over 2,0 x 109 CFU/mL showed the same immunizing power as the three commercial vaccines used for comparison purposes. Observations about the inhibitory effects of metabolites accumulation and substrate saturation on the microorganism growth pointed the fed-batch as a promising operation mode to produce larger amounts of biomass. Cellular concentrations reached in the experiment ran under these condition were increased around five times.
Keywords: Engenharia bioquímica; Biotecnologia - indústria; Proteínas - biotecnologia; Vacina; Biorreatores; Otimização; Erysipelothrix rhusiopathiae; Swine erysipelas; Aeration conditions; Optimization of bioreactor cultivation; Vaccines; SpaA.; OUTROS